Modern Capabilities of Radiological and Endoscopic Diagnosis of Müllerian Anomalies - Erkinovna, Makhmudova Sevara (American Journal of Biomedicine and Pharmacy, 2025)
Congenital sexual anomalies often lead to serious disorders of the reproductive system and are associated with a poor prognosis for childbirth. However, in recent years, due to the active development of assisted reproductive technologies, it has become possible to significantly improve reproductive outcomes in infertile patients. The main factor in successful treatment in such cases remains timely and accurate diagnosis of congenital anomalies, as well as well-structured tactics for managing such patients. The article reviews clinical, instrumental and laboratory diagnostic methods, including ultrasound, MRI, endoscopic methods, as well as molecular genetic studies, which allow not only to identify the anomaly, but also to determine its etiology.